Chennakeshava temple, Beluru, Life-size sculptures of Gods and Goddesses, p22 - Brig Ajai Singh (2021)
Image courtesy: Brig A.P. Singh - www.collectingmoments.in; Image courtesy: Brig A.P. Singh - www.collectingmoments.in